Genetic Variability of GCKR Alters Lipid Profiles in Children with Monogenic and Autoimmune Diabetes - Tracz, A.; Madzio, J.; Gnys, P.; Malachowska, B.; Borowiec, M.; Wyka, K.; Jarosz-Chobot, P.; Mysliwiec, M.; Szadkowska, A.; Mlynarski, W.; Fendler, W.; on behalf of the PolPeDiab Study Group (Experimental and Clinical Endocrinology & Diabetes, 2014)
Purpose: Mutations in the glucokinase (GCK) gene are associated with altered blood glucose and lipid concentrations. Our aim was to assess the effects on HbA1c and serum lipid levels of single nucleotide polymorphisms (SNPs) in 2 genes encoding proteins that interact with glucokinase: glucose-6-phospatase catalytic subunit 2 (G6PC2) and glucokinase regulatory protein (GCKR).Methods: The study group included 129 children with GCK-MODY from the Polish Registry of Monogenic Diabetes and 395 with type 1 diabetes (T1DM), in whom we genotyped 2 SNPs in G6PC2 (rs560887) and GCKR (rs1260326). Lipid concentrations were assessed in fasting serum samples.Results: Total and HDL cholesterol concentrations were significantly lower in the GCK-MODY group than in patients with T1DM (167.5±32.5 mg/dl vs. 174.4±31.1 mg/dl, p=0.0435 and 48.42±14.3 mg/dl vs. 58.7±12.7 mg/dl, p<0.0001, respectively). No differences in genotype distributions were found except for underrepresentation of GCKR TT homozygotes among GCK-MODY patients (10.9% in GCK-MODY vs. 17.7% in T1DM, p=0.0651). GCKR genotypes showed significant associations with lipid profiles and HbA1c levels, whereas no such associations were noted for G6PC2. After adjustment for confounders, TT homozygotes were shown to have higher total cholesterol and marginally higher LDL cholesterol and triglyceride levels (p=0.0245, p=0.0657 and p=0.0550, respectively). The difference between TT homozygotes and other genotypes was similar in magnitude within the GCK-MODY and T1DM groups. No significant interactions between the type of diabetes and the GCKR or G6PC2 genotype were detected.Conclusions: Individuals who are homozygous TT at rs1260326 of the GCKR gene have higher triglyceride, total and LDL cholesterol levels regardless of the presence of GCK mutations.
Keywords: diabetes; fatty acid synthesis; MODY